Genetic analysis reveals conspecificity of two nominal species of Anaphes fairyflies (Hymenoptera: Mymaridae), egg parasitoids of Oulema leaf beetle (Coleoptera: Chrysomelidae) pests of cereal crops in Europe and of rice in East Asia - Triapitsyn, S V; Rugman-Jones, P F; Kusuhara, H; Nakano, R; Janšta, P; Arikawa, S; Adachi-Hagimori, T (PloS one, 2023)
Anaphes (Anaphes) flavipes (Foerster), a fairyfly (Hymenoptera: Mymaridae) native of Europe, is an economically important egg parasitoid for the natural control of Oulema spp. leaf beetle (Coleoptera: Chrysomelidae) pests of cereal crops such as barley, oats, rye, and wheat in Europe, and for the classical biological control of the invasive Oulema melanopus (L.) in North America. A morphologically very similar Anaphes (Anaphes) nipponicus Kuwayama, known from mainland China, Japan, Republic of Korea, Far East of Russia and Taiwan, is an egg parasitoid of Oulema oryzae (Kuwayama), a pest of rice mainly in temperate parts of East Asia. The nuclear 28S-D2 and ITS2 and the mitochondrial COI genes were used as markers to compare specimens of A. (Anaphes) flavipes reared from eggs of an Oulema sp. on barley in Germany with those of A. (Anaphes) nipponicus reared from eggs of O. oryzae on rice in Honshu Island, Japan. Because the resulting sequences are practically identical, within an expected intraspecific genetic variability, conspecificity of these two nominal species has been confirmed, and consequently A. (Anaphes) nipponicus Kuwayama, 1932, syn. n. is synonymized with A. (Anaphes) flavipes (Foerster, 1841). Taxonomic notes and illustrations are provided for the specimens of both sexes of A. (Anaphes) flavipes from Japan to facilitate their recognition.
Keywords: brouci; Avena; Europe; Evropa; rýže (rod); mužské pohlaví; Hordeum; Hymenoptera; ječmen (rod); Dálný východ; ženské pohlaví; oves; zvířata; Asia, Eastern; Coleoptera; Edible Grain; Oryza; Female; jedlá semena; Male; Animals